Prayer and Paradox in Baudelaire. Issue 2 (July 2019) - Toumayan, Alain
Abstract : It is well attested that Baudelaire took religious discourse very seriously and that it informs much of his poetic practice. The rhetorical form of prayer and the figure of paradox are two specific instances in which Baudelaire's appropriation, rewriting, and transformation of religious discourse can be assayed. In this article, I examine first the incidence of prayer as a form and theme in Baudelaire's writings. In a second portion of the essay, I examine the specific figure of paradox which is a common feature particularly of the prose poems. While paradox and the figure of oxymoron are very prevalent throughout Baudelaire's œuvre, I consider the specific case of paradox in theological writing. The third portion – and focus – of my essay relates these two lines of inquiry in an analysis of the prose poem 'Le Joueur généreux' in which the prayer form itself becomes paradox.